Mega-regional trade Agreements: Costly distractions for developing countries? - Badri G. Narayanan; Sangeeta Khorana (Journal of Economic Structures, 2017)
This paper examines the relationship between mega-regional trade Agreements and diet-related health given that such Agreements aim to liberalize 'substantially all trade and investment' that could potentially impact on health through tariff elimination and stronger intellectual property commitments in partner countries. We analyse two interlinked policy concerns: first, how tariff reduction/elimination under mega-regional Agreements impact on the production of sugar? Second, how mega-regional Agreements with Trade-Related Aspects of Intellectual Property Rights (TRIPS)-style and TRIPS-plus commitments modify intellectual property rules among partner countries and impact on developing countries' access to life-saving drugs and medicines? Using a dynamic Global Trade Analysis Project model, we find there are significant health consequences of trade commitments undertaken by developing countries with potential detrimental health effect on populations such that first, higher production of sugar alters consumption trends. Second, despite stricter intellectual property rules, which result in net global gains, developing countries suffer from the regulatory chill effect.
Keywords: I18; F15; F13; 330; Government policy; Economic integration; Trade policy